A case study on visual spatial skills and level of geometric thinking in learning 3D geometry among high achievers - Abd. Wahab, Rohani (Serials Publications, 2016)
Since geometry mainly comprises of three-dimensional (3 D), visual spatial skills and level of geometric thinking are essential in the teaching and learning of Geometry. In addition, it is also important in other fields, such as engineering, design, graphics, film, science, chemistry, business and arts. Visual spatial skills comprise the ability to imagine, illustrate and describe visual process happens in the mind. Visual spatial skills and levels of geometric thinking have been claimed to cause difficulties in the learning of geometry. Therefore, this case study was conducted to assess students' visual spatial skills and level of geometric thinking among high achievers. A total of 133 respondents participated in this study, which consisted of 62 male and 71 female respondents. The study used a testing tool which can measure visual spatial skills performance. The testing tool measured five visual spatial abilities, such as combining 2-D, rotation, view, manipulation, and cut. Visual spatial skills were tested using a standard Spatial Visualization Mental Test: Purdue Spatial Visualization Tests of Rotation of Development (PSVT: D), Purdue Spatial Visualization Tests of Rotation (PSVT: R), Purdue Spatial Visualization Tests of View (PSVT: V), Transformation 3D to 2D test (T3D2DT), and Mental Cutting Test (MCT), while the van Hiele Geometric Thinking Test (vHGT) was employed to find out the level of students' geometric thinking. Data in the forms of frequency, mean, and percentage were presented using graphs and tables. The results indicated that the students' levels of mental ability in rotation, view, and cut were low. On top of that, the students' level of geometrical thinking was found at a level of concern as majority of the students were at lowest level (Level L1). Findings retrieved from the study are described in detail in this paper.